A personal leadership statement (2025)
This statement purpose is to explain how leadership and empowerment impact in the foreign language classroom, focusing on integral leadership. Leadership is often defined as a collaborative work in which a guide takes the lead and monitors followers’ performance. However, in this fast-changing world, an approach that leverages all human complexities and foster diversity in teamwork. Wherefore, the concept of integral leadership incorporates physical, emotional, mental and spiritual dimensions that are considered to guide others towards share goals, which entails trusting the group’s abilities individually and collectively. This perspective empowers teachers to create a learning environment in which support, innovation and autonomy are promoted, aiming to empower not only students but other teachers and the whole educational community to put into practice their talents and skill, and keep improving while working on set goals.